Afro-descendants in Latin America Toward a Framework of Inclusion - Freire, German (World Bank E-Library Archive, 2018)
About one in four Latin Americans self-identify as Afro-descendants today. They comprise a highly heterogeneous population and are unevenly distributed across the region, but share a common history of displacement and exclusion. Despite significant gains over the past decade, Afro-descendants still are overrepresented among the poor and are underrepresented in decision-making positions, both in the private and the public sector. The extent to which Latin America will be able to end extreme poverty and boost shared prosperity will therefore depend, to a very large degree, on the social inclusion of Afro-descendants. The objective of this study is to deepen the region's empirical understanding of the drivers behind the persistent exclusion of the afro-descendants, as a first step to design appropriate solutions. The report proposes a framework to organize and think of the myriad options available to address their situations, based on the experience accumulated by the region and the data available